Jaringan dan Kiprah Orang Arab di Teluk Palu, 1830-1930 - Sairin, Mohammad (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
This paper discusses the life of Arabs in Palu Bay in 1830-1930. There are two aspects thatmust be investigated, namely how the Arabs network in Palu Bay and how they contribute to thecommunity in Palu Bay. This paper used historical method by using oral sources and written sources.Oral sources are through interviews with Arab families in Palu while written sources were archives ofofficial colonial government publications, manuscripts, books, journals and scientific works. Thefindings in this study are: First, Arabs in Palu Bay have kinship networks and trade networks with otherregions in the archipelago such as Makassar, Manado, Bolaang Mongondow, Buol, Tomini Bay, Java,Kalimantan and Singapore. They also formed a kinship network by marrying local noblewomen. Second,the gait and contribution of Arabs in Palu Bay can be seen from their activities in the field of da'wah andIslamic symbols, politics, and the economy. Their presence has left a cultural heritage, includingmosques, schools, and maulid ceremonies.